Killing Kennedy : The End of Camelot - O'Reilly, Bill; Dugard, Martin (New York : Henry Holt and Company, 2012)
Recounts the murder of John Fitzgerald Kennedy and how gunshots on a Dallas afternoon not only killed a beloved president but also sent the nation into the cataclysmic division of the Vietnam War and its culture-changing aftermath.
Includes bibliographical references (pages [305]-311) and index.
Keywords: Kennedy, John F -- 1917-1963 -- Assassination